A proximity-allosteric Adapter unlocks Cas12a exponential amplification for versatile homogeneous assay - Feiyu Chen; Man Tang; Zhangling Liu; Wuxian Li; Xingping Hu; Linguo Xiang; Lanxin Jiang; Yanna Ban; Jing Wang; Jia Li; Wei Cheng; Tiantian Yang (Analytica Chimica Acta, 2026)

A state-of-the-art review in legume protein gelation: mechanisms, structure-function relationships, modification strategies, and emerging food applications - Xiangxiao Kong; Wenting Tang; Man Li; Qingjie Sun; Chuanfen Pu (Food Research International, 2026)

PD-1/PD-L1 inhibition after cryoablation is associated with improved tumor control and immunosuppressive microenvironment remodeling in Lewis lung adenocarcinoma - Qi Liu; Shuo Zhang; Xuxin Chen; Jiao Li; Man Qi; Yongqun Li; Yiwei Ding; Xiaoyu Zhao; Jun Shi; Jiajia Tang; Meng Liu; Xue Wang; et al. (Cryobiology, 2026)

Cellular Responses to Cold Stress in Pampus argenteus: Involvement of Dusp5 in MAPK Signaling, Apoptosis Suppression, and Organelle Protection - Mengke Tang; Man Zhang; Yubei Qiu; Yuanbo Li; Qinqin Dai; Xianglong Chen; Chongyang Wang; Fangjun Xu; Lu Zhang; Zi Yuan; Xiaojun Yan; Jiabao Hu; et al. (Marine Biotechnology, 2026)

Quercetin exerts radioprotective effects against radiation-induced intestinal injury with involvement of the PI3K-AKT/Caspase-3 axis - Qing Guo; Zhibing Tang; Zhenyu Hou; Ge Yan; Jiaxuan Wang; Man Zhang; Ruige Ma; Juan Wang; Qiong Feng; Zhen Wang; Chunlei Wang; Lin Zhao (Molecular and Cellular Biochemistry, 2026)

The phytosulfokine receptor ClPSKR1 negatively regulates watermelon resistance to Fusarium wilt - Chunmei Xie; Rong Tang; Man Zhang (Physiological and Molecular Plant Pathology, 2026)

LIDAR-based visibility map for plan position indicator (PPI) scans and range height indicator (RHI) scans – methodology and observations in two uncommon haze cases in Hong Kong - Man Lok Chong; Ping Cheung; Wai Ho Tang; Chun Kit Ho; Pak Wai Chan (Atmospheric Environment, 2026)

Limit Analysis of Uplift Stability of CAES Rock Cavern Considering Crack Initiation and Groundwater - Jia Pan; Caichu Xia; Man Huang; Yunjin Hu; Zhicheng Tang (Rock Mechanics and Rock Engineering, 2026)

Transition metal-loaded granular activated carbon as efficient three-dimensional electrode for humic acid removal - Jianhong Jiang; Man Yang; Min Huang; Xinyao Guo; Xia Tao; Li Xu; Yue Lu; Lin Tang; Yi Cheng (Journal of Environmental Sciences, 2026)

Differences in DHA stability of DHA-enriched yogurts during low-temperature storage - Senyang Hu; Jianmin Zou; Hejing Tang; Wenhua Jin; Jian He; Zihao Wang; Yang Yang; Chang Liu; Pengjie Wang; Wei Tan; Ignatius Man-Yau Szeto; Xiaoyu Wang; et al. (Food Research International, 2026)

Casein-liposome complex loading basil essential oil: Preparation, antibacterial effect, and preservative effect on braised beef - Yunshuang Man; Hui Tang; Yudi Wang; Rongrong Yang; Dongling Yan; Qianqian Yu; Lang Zhang; Lin Mei; Jun Qi; Lele Shao (Food Chemistry, 2026)

Peak shear strength of rock discontinuities in the near-surface: Criteria, influencing factors, challenges, and perspectives - Shigui Du; Man Huang; Rui Yong; Nick Barton; Zhicheng Tang (Engineering Geology, 2026)

The F-box protein ZmFBK1 facilitates autophagy-mediated degradation of maize NLR protein Rp1-D21 to suppress the hypersensitive response - Chang-Xiao Tang; Shi-Jun Ma; Qi-Dong Ge; Yang Sun; Tong-Tong Liu; Man Yang; Zi-Xuan Kang; Yu-Chen Dai; Xuan Zhang; Xueman Liu; Yanyong Cao; Guan-Feng Wang (Molecular Plant, 2026)

Slope and grain size control on channel-levee development in mixed turbidite-contourite systems - Long He; Tao Jiang; Man Tang; Dongmei Tian; Licheng Cao; Cong Cheng (Marine Geology, 2026)

Model-based assessment of impacts of aeration intensity on the water-energy-carbon nexus of a full-scale wastewater treatment plant - Xinhong Han; Lu-Man Jiang; Lifeng Lin; Long Wang; Peng Peng; Jiaming Hu; Jiguang Ying; Yi Yang; Rui Tang; Zhen Zhou (Journal of Environmental Management, 2026)

Tuning d-f hybridization to mimic haloperoxidase for microneedle-assisted targeted therapy of drug-resistant infections - Zhichao Yu; Fengrui Gao; Minglang Zou; Man Xu; Sufang Liu; Da Huang; Zuquan Weng; Yongyi Zeng; Dianping Tang; Xiaolong Liu (Chemical Engineering Journal, 2026)

Enhancement of infrared radiation and heat dissipation functionality of MnSe2 2D magnet via lattice engineering - Man Wang; Xiaolei Nie; Tonglu Huang; Wanting Zhu; Yu Zhang; Mingrui Liu; Zhixin Tang; Wenyu Zhao (Chemical Engineering Journal, 2026)

Construction of recombinant Lactococcus lactis expressing VP1 from duck hepatitis a virus types 1 and 3 and evaluation of its immune effect - Yafei Qin; Yaru Fan; Meijuan Zhang; Saisai Zhao; Xinhong Man; Dalin He; Youxiang Diao; Junxun Li; Jingdong Hu; Yi Tang (Veterinary Research Communications, 2026)

Coalescence of a subcritical crack pair in carbonate rocks upon acidizing - Xiao-Jie Tang; Si-Han Zhou; Man-Man Hu (International Journal of Rock Mechanics and Mining Sciences, 2026)

Synergistic effects of heating and ultrasonic co-treatment on pea protein functionality: Self-assembled protein carriers for enhanced resveratrol solubility - Lihua Tang; Qinhao Guan; Yuan Wang; Man Xu (Food Hydrocolloids, 2026)

Adiponectin attenuates atherosclerosis via macrophage polarization-mediated T Cell exhaustion by modulating the NF-κB p65/PI3K/Akt signaling pathway - Man Qin; Sufang Xu; Yuefeng Chen; Xiaoxiao Luo; Xiaolei Tang; Liang Zhang; Qin Xu (Tissue and Cell, 2026)

Synergistic effects of photoinduced reactive oxygen species and electrons enhance nitrous oxide emissions from irradiated soil - Xiangyu Chen; Shaofu Huang; Yang Li; Xiuwen Zhang; Haiyang Shao; Xiang Tang; Raymond Jianxiong Zeng; Man Chen (Journal of Hazardous Materials, 2026)

Coupled effects of biochar nanoparticles aging and transport on rare earth element immobilization and carbon sequestration - Quan Wan; Miaoyue Zhang; Beibei Liu; Erwin Klumpp; Roland Bol; Yuan Dai; Man Zhao; Shizhong Wang; Yetao Tang; Jean Louis Morel; Stéphanie Ouvrard; Chao Jin; et al. (Journal of Environmental Sciences, 2026)

Residential greenness and metabolic syndrome among older adults: exploring the mediating effects of physical activity and sedentary time - Shuhui Dai; Lu Fang; Yuting Zhang; Hazizi Duoliken; Man Rao; Jiayi Li; Shanshan Yin; Mingjuan Jin; Jianbing Wang; Kun Chen; Mengling Tang (Environmental Research, 2026)

Glycine Drives IMP Production in Hybrid Bream (Megalobrama Amblycephala ♀ × Culter Alburnus ♂) Via Concerted Action: Activating glycyl-tRNA Synthetase and Fueling the Pentose Phosphate Pathway - Zhehua Xu; Weiting Zhang; Ruijie Zhan; Jiefan Zhou; Man Chen; Yonghua Zhou; Fufa Qu; Rong Zhou; Shaochun Liu; Shenping Cao; Jianzhou Tang; Zhen Liu (Marine Biotechnology, 2026)

Deep Learning-Based Object Detection of Electromagnetic Interference Echoes from Weather Radar Data - Man Yao; Muyun Du; Rong Yu; Xianling Jiang; Hedi Ma; Guoying Tang; Peiting Liu (Journal of Meteorological Research, 2026)

Engineered hydrogels for siRNA delivery: From smart design to therapeutic impact - Shaohui Geng; Yijin Jiang; Huawei Wang; Anqi Liu; Xiuwen Wang; Ran Man; Jingyuan Fu; Yiwei Guan; Zi Ye; Zixuan Shu; Han Sheng; Jinian Wei; et al. (Chemical Engineering Journal, 2026)

Microbial mediators in plant-vole interactions: Linking grassland plant traits and gut microbiota for conservation of Brandt’s voles - Jing Wang; Changkang Li; Yanling Wu; Xiaomei Zhao; Duhu Man; Yifeng Zhang; Baohong Tang; Jiqi Lu (Biological Conservation, 2026)

Targeted screening of pancreatic lipase inhibitory peptides from quinoa protein hydrolysates by ligand fishing - Zeyue Fu; Junhao Wang; Chunxiao Wu; Jinfan Qin; Byung-Hoo Lee; Man Li; Qingjie Sun; Wenting Tang (Food Chemistry, 2025)

DFT-enhanced machine learning for accurate PLQY prediction and inverse design of novel MR-TADF materials - Haochen Shi; Yiming Shi; Guangjun Zeng; Haichang Wang; Yumei Hu; Bo Qiao; Zhiqin Liang; Suling Zhao; Man-Chung Tang; Dandan Song (Chemical Engineering Journal, 2025)

Selective kernel convolution with global attention mechanism for multitask change detection in optical and SAR images - Tonggen Yang; Liang Huang; Bo-Hui Tang; Zhitao Fu; Zhen Zhang; Zhongxi Ge; Man Zhang; Siming Pu (Earth Science Informatics, 2025)

Targeting MAPK10 with gga-miR-222b-5p suppresses apoptosis in DF-1 cells infected with the avian reticuloendotheliosis virus strain SNV(REV-SNV) - Qing Zhang; Yubo Zhao; Saisai Zhao; Xinhong Man; Shumin Yu; Youxiang Diao; Yi Tang; Jingdong Hu (Veterinary Microbiology, 2025)

Pollution sources, characteristics and environmental risk assessment of heavy metals in surface water and sediments of typical pyrite mine in Southwest China - Ziqiu Nie; Jiabin Luo; Jie Tang; Bo Li; Bohan Chen; Man Gao; Xingjie Wang; Liu Guo (Journal of Environmental Sciences, 2025)

Amino acid promotes the formation of enals and 1-octen-3-ol from linoleic acid during the thermal reaction between alanine-xylose Amadori compound and Agrocybe aegerita enzymatic hydrolysates - Tong Zhou; Qingqing Chai; Man Zhang; Heping Cui; Mingzhou Song; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Bioscience, 2025)

Liposome-delivered natural antimicrobials in foods: Antibacterial efficacy and mechanisms - Dongling Yan; Yudi Wang; Rongrong Yang; Yunshuang Man; Hui Tang; Qianqian Yu; Lele Shao (Food Bioscience, 2025)

High-efficiency SrTiO₃@SiC catalytic ceramic membrane with photocatalytic self-cleaning for enhanced tetracycline degradation and fouling resistance in wastewater treatment - Rongqi Xu; Dandan Tang; Yu Tian; Yichuan Xu; Kexin Hu; Xiaolei Wang; Zhengqian Wen; Jiayou Ji; Changlian Chen; Shulin Wang; Li Zhu; Man Xu (Chemical Engineering Journal, 2025)

A self-floating bacterial cellulose supported MoS2@MWCNTs-OH evaporator with efficient salt resistance, antibacterial properties, and selective adsorption - Xiaohua Yang; Man Zhou; Yihang Tang; Jing Li; Lifu Zhou; Wentao Xu; Yao Xiao; Jin Zhao; Yuzhe Zhang; Zhongyu Li (Chemical Engineering Journal, 2025)

Multifunctional textiles with bimetallic MOFs for enhanced ammonia uptake and protective applications - Yajie Shu; Zimeng Sheng; Danni Wang; Hao Gu; Yumeng Tang; Guangsheng Zhu; Man Zhang; Jinfeng Wang; Jinming Zhang; Haibao Huang (Chemical Engineering Journal, 2025)

Recent advances in non-precious metal electrocatalysts for anion exchange membrane water electrolysis: Mechanistic insights, catalyst design, and structural regulation strategies - Qing Wang; Yuan Wang; Hon Man Luk; Jihui Tang; Shuang Wu; Dongyang Wu; Zhongyuan Hu; Da Cui; Jinghui Zhang (Chemical Engineering Journal, 2025)

Cumulative exposure to the chemical components of PM2.5 and the prevalence of Anemia: Insights from a large group of workers in South China - Xinyue Li; Zhiqiang Li; Yongqing Sun; Man Zhang; Meimei Zhong; Yueqian Wu; Xudan Chen; Xurui Sun; Dan Chen; Huanle Cai; Guanghui Dong; Hui Tang; et al. (Atmospheric Environment, 2025)

Change detection in optical and SAR images by integrating fine-grained feature extraction and contextual transformation - Man Zhang; Liang Huang; Bohui Tang; Tonggen Yang; Siming Pu (Advances in Space Research, 2025)

Whole-genome resequencing and transcriptomes analysis of hermaphroditism mechanisms in silver pomfret (Pampus argenteus): The role of feeding and lipid metabolism - Yaya Li; Jiabao Hu; Chongyang Wang; Shipan Zhao; Man Zhang; Youyi Zhang; Yuanbo Li; Qingqing Dai; Mengke Tang; Chunlai Qin; Zukang Feng; Shanliang Xu; et al. (Aquaculture, 2025)

Citric acid as a green rejuvenator: mechanistic insights into the complete recovery of floatability for oxidized arsenopyrite - Jincheng Ran; Xinyan Wu; Wen Tang; Yipeng Zuo; Man Jiang; Enxia Gao; Baoxu Song (Journal of Cleaner Production, 2025)

Isolation of two new isomers of fusarin D from Fusarium sp. G10, an endophytic fungus of Iris japonica - Ya-Nan An; An-Le Tan; Xiao-Ying Long; Yue Zhou; Man He; Xiao-Long Tang (Natural Product Research, 2025)

Spatiotemporal evolution and influencing factors of Resource-Environment pressure: a case of the new Western Land-Sea corridor in China - Yan Tang; Shan Gao; Yunpei Cheng; Man Xiao; Tian Hao; Xinzhi Wang (Environment, Development and Sustainability, 2025)

Ultrasensitive, portable and multiplexed molecular detection of pathogenic bacteria in a cross-validating manner via Argonaute-triggered and reverse-phase enhanced fluorescent lateral flow bioassay - Xiaoqin Tang; Xinyue Li; Yuhan Tian; Qiang Zhang; Shuli Man; Weipan Peng; Long Ma (Journal of Hazardous Materials, 2025)

Role of exogenous xylose during its co-heating with alanine-xylose Amadori compound: Competitively promoting 2-furfural formation and limiting pyrazines generation - Tong Zhou; Qingqing Chai; Man Zhang; Heping Cui; Ahmad Mohammad; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Chemistry, 2025)

Surface Temperature Influenced by Downward Longwave Radiation Is the Main Driver of Deglaciation in Central Asia - Wenhui Tang; Xinfeng Wu; Feng Chen; Wenmin Man; Weipeng Yue; Shijie Wang; Youping Chen; Heli Zhang (International Journal of Climatology, 2025)
The economy and society of Central Asia depend heavily on glacier meltwater from the Tien Shan as a water resource. However, recent global warming has altered the regional climate and melting patterns of glaciers, and an unprecedented trend of glacier retreat caused by rapid warming has been observed in the Tien Shan since the 1970s. While short‐term monitoring and climate response of glaciers are well developed, less effort has been devoted to long‐term historical fluctuations and physical mechanism studies based on climate models. Here we use a tree‐ring reconstruction and melting energy simulated by an energy balance model to study the glacier mass balance of Urumqi Glacier No. 1 for the past 400 years, with the aim of better understanding the long‐term changes in the relationship between this glacier and climate change during the summer ablation period. Our results demonstrated that surface temperature change driven by downward longwave radiation is the dominant factor affecting long‐term glacier melting. Against the background of climatic warming and humidification in northwest China, the increase in precipitation is unable to offset the melting trend caused by rising temperatures. Further analysis revealed that the dominant driver of glacier melting is the warming effect of greenhouse gas forcing. Also, aerosol forcing causes glacier melting via direct and indirect radiation effects. These findings emphasise the importance of monitoring the regional glaciers, combined with climate change research, to establish a scientific foundation for water management and environmental conservation in Central Asia.

A crystalline triazine covalent organic framework with partial fluorination for efficient hydrogen peroxide production toward water treatment - Limin Jin; Man Deng; Jun Gao; Lichao Wang; Qi Zhou; Xiujuan Tang; Qiang Li; Hao Du; Derek Hao; Qi Wang (Chemical Engineering Journal, 2025)

Ligand-rich oxygen evolution electrocatalysts reconstructed from metal-organic frameworks for anion-exchange membrane water electrolysis - Shiqi Li; Weiwei Liu; Yi Shi; Tang Wang; Tianyang Liu; Xiang Xue; Rui Li; Man Qiao; Zhen-Yu Wu; Wang Zhang (Science Bulletin, 2025)

Comprehensive mechanisms of epigallocatechin-3-gallate (EGCG) metabolism during tea dieback disease infection in tea plant (Camellia sinensis) - Yiyong Chen; Bo Zhou; Jianlong Li; Man Zhang; Yingying Cui; Jinchi Tang (Food Bioscience, 2025)

The response and ecological implications between various sulfur forms and environmental factors in acid mine drainage - Man Gao; Jie Tang; Yujiao Tu; Mingtan Zhu; Ziqiu Nie; Xin Liu; Guo Liu (Environmental Research, 2025)

Lophatherum-Gracile driven near-infrared carbon dots inhibit ferroptosis and mitophagy to treat acute kidney injury - Lijuan Yang; Fan Dai; Haitian Tang; Man Li; Yibo An; Yubo Tan; Renyuan Liu; Xinyu Tan; Wenxiang Zhang; Syed Faheem Askari Rizvi; Junjie Zou; Zhixiang Lu; et al. (Chemical Engineering Journal, 2025)

Roseateles cavernae sp. nov., a Bacterium Isolated from Freshwater of the Old Huanglong Cave in Yunnan Province, South-West China - Yu-Man Zhang; Qian Jiang; Mu-Yao Li; Qing-Yu Miao; Yi-Qing Li; Min Yin; Cui-Ping Miao; Shu-Kun Tang (Current Microbiology, 2025)

Identification and characterization of dual specificity phosphatase genes (DUSP) in silver pomfret (Pampus argenteus): Protective effects of DUSP1 and DUSP5 against cold stress - Mengke Tang; Man Zhang; Jiabao Hu; Yubei Qiu; Youyi Zhang; Yaya Li; Yuanbo Li; Qinqin Dai; Shangliang Xu; Lu Zhang; Zi Yuan; Yajun Wang (Aquaculture, 2025)

Prevalence of Clostridium perfringens in sheep (Ovis aries) and goat (Capra hircus) populations across Asia: A systematic review and meta-analysis - Wen-Xu Tan; Tong Ye; Qi-Man Zhang; Miao Zhang; Xiao-Tong Chen; Lu-Yao Tang; Meng-Ting Yang; Jing Jiang; Quan Zhao (Research in Veterinary Science, 2025)

Enhanced removal of gatifloxacin by Fe3O4@bacteria: Performance and mechanism - Jianfu Man; Xinran Wang; Wenpeng Jia; Yongzheng Tang; Yongrui Pi (Process Safety and Environmental Protection, 2025)

Exposure to toxic metals might accelerate aging - Wenqing Wang; Kaixuan Yang; Jiayi Li; Yaoyao Lin; Man Rao; Yuting Zhang; Hazizi Duoliken; Mingjuan Jin; Jianbing Wang; Kun Chen; Mengling Tang (Environmental Research, 2025)

Non-noble CeO2/CdS/NiS heterojunction for photoredox-catalyzed plastic waste selective synthesis and hydrogen production from natural seawater - Ziwen Wang; Qiuyu Wang; Zhe Yin; Man Zhang; Guoping Yu; Qingcheng Luo; Huanyu Chen; Binglin Tang; Kangzheng Li; Zhichao Zhang; Bo Lv (Fuel, 2025)

Effects of Blood Cadmium Levels on Blood Pressure and the Risk of Hypertension in a Community-Based Elderly Population - Man Rao; Yuting Zhang; Hazizi Duoliken; Sitong Li; Mingjuan Jin; Jianbing Wang; Kun Chen; Mengling Tang (Exposure and Health, 2025)

Diagnostic accuracy of Xpert MTB/RIF Ultra for detecting pulmonary tuberculosis and rifampicin resistance: a systematic review and meta-analysis - Man-Qing Wang; Ya-Fang Zheng; Yu-Qi Hu; Jin-Xia Huang; Zi-Xin Yuan; Zu-Yan Wu; Lu-Fang Huang; Chu-Ting Tang; Feng-Yi Zhang; Yan Chen; Jin-Ke He; Xu-Guang Guo; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Seismic performance and repairability assessment of resilient RAC frame structures employing UHSB in columns - Weiheng Liu; Jianwei Zhang; Man Zhang; Lin Tang (Bulletin of Earthquake Engineering, 2025)

Correction: Tumor-Targeted Chemoimmunotherapy with Immune-Checkpoint Blockade for Enhanced Anti-Melanoma Efficacy - Man Li; Yuting Yang; Chaoqun Xu; Jiaojie Wei; Yingke Liu; Xingli Cun; Qianwen Yu; Xian Tang; Sheng Yin; Zhirong Zhang; Qin He (The AAPS Journal, 2025)

Mechanism of removal of Sb from printing and dyeing wastewater by a novel titanium-manganese binary oxide - Zhiquan Xiang; Yijie Zhang; Zhuowei Shen; Dan Wang; Zhiqiang Shen; Yaoyu Tang; Lei Bo; Man Wang (Environmental Research, 2025)

Efficient lithium-oxygen batteries with low charge overpotential via solid-state design and thermal catalyst activation - Xing Tang; Yu Wang; Xiangyu Wen; Yuanguo Wu; Zining Man; Weiting Qi; Jiaqi Wang; Zhe Lü; Xingbao Zhu; Yugui Yao (Chemical Engineering Journal, 2025)

A ternary dumbbell MoS2 tipped Zn0.1Cd0.9S nanorods visible light driven photocatalyst for simultaneous hydrogen production with organics degradation in wastewater - Muhammad Tayyab; Yaoshu Xie; Xianjun Tan; Muhammad Usman; Man-Chung Tang; Season Si Chen (Chemical Engineering Journal, 2025)

Effects of supplemental medusa ( Rhopilema esculentum ) on intestinal microbiota and metabolites in silver pomfret ( Pampus argenteus ) - Man Zhang; Mengke Tang; Kaiheng Yan; Youyi Zhang; Yaya Li; Jie Tang; Shanliang Xu; Xiaojun Yan; Jiabao Hu; Yajun Wang (Journal of Fish Biology, 2025)
Pampus argenteus demonstrates a preference for Rhopilema esculentum as prey, yet the ramifications of consuming supplemental medusa on fish microbiota and metabolism remain elusive. To elucidate these effects, 300 juvenile fish were divided into two groups: control group (C, given commercial food only) and supplemental medusa (SM) group (given supplemental medusa + commercial feed). After 15 days, fish in the SM group exhibited a significant increase in fatness, the amylase activity in the intestine significantly increased, and the intestinal microvilli were arranged more neatly. The comprehensive approach involving 16S rRNA amplicon sequencing and metabolomics was employed, leading to the identification of five genera within the SM group, namely Lactococcus , Cohaesibacter , Maritalea , Sulfitobacter , and Carnobacterium . Functional prediction analysis of the microbiota indicated that the consumption of supplemental medusa facilitated processes such as glycolysis/gluconeogenesis and amino acid absorption. Metabolomics analysis revealed significant enrichment of 85 differential metabolites, most of them belonging to fatty acids and conjugates. These differential metabolites primarily participated in processes such as amino acid metabolism, fatty acid synthesis, and disease. Notably, the consumption of medusa resulted in a significant reduction in nine lysophospholipids associated with cardiovascular disease and inflammation. Pearson's correlation coefficient analysis revealed associations between specific microorganisms and metabolites, indicating that Cobetia , Weissella , and Macrococcus exhibited an increased abundance in the SM group, positively correlating with apocynin, 12‐Hete, and delta 9‐THC‐d3. The indicator bacteria Psychrobacter reduced in the SM group, exhibiting a negative correlation with cystathionine (a compound involved in glutathione synthesis). Overall, the supplementation of medusa may confer a beneficial effect on the immunity of the fish. This study contributes to the theoretical framework for fish feed development.

Inactivation and sublethal injury of Salmonella Typhimurium on beef and in aqueous solution treated with lactic acid - Yunshuang Man; Mengjiao Zhang; Hui Tang; Rui Wen; Rongrong Yang; Lin Mei; Jun Qi; Ruitong Dai; Guoyuan Xiong; Lele Shao (Food Research International, 2025)

Determinants of soundscape quality of communal open space in Hong Kong - Minqi LIN; Chi Kwan CHAU; Shiu Keung TANG; Wai Kit CHUNG; Ho Man YU (Building and Environment, 2025)

Effect of Post-transplant Dietary Restriction on Hematopoietic Reconstitution and Maintenance of Reconstitution Capacity of Hematopoietic Stem Cells - Si Tao; Xingxing Qiu; Yiting Wang; Rongrong Qiu; Chenghui Yu; Man Sun; Lulu Liu; Zhendong Tao; Liu Zhang; Duozhuang Tang (Stem Cell Reviews and Reports, 2025)
Hematopoietic cell transplantation (HCT) is an important therapy for many hematological malignancies as well as some non-malignant diseases. Post-transplant hematopoiesis is affected by multiple factors, and the mechanisms of delayed post-transplant hematopoiesis remain poorly understood. Patients undergoing HCT often suffer from significantly reduced food intake due to complications induced by preconditioning treatments. Here, we used a dietary restriction (DR) mouse model to study the effect of post-transplant dietary reduction on hematopoiesis and hematopoietic stem cells (HSCs). We found that post-transplant DR significantly inhibited both lymphopoiesis and myelopoiesis in the primary recipient mice. However, when bone marrow cells (BMCs) from the primary recipient mice were serially transplanted into secondary and tertiary recipient mice, the HSCs derived from the primary recipient mice, which were exposed to post-transplant DR, exhibited a much higher reconstitution capacity. Transplantation experiments with purified HSCs showed that post-transplant DR greatly inhibited hematopoietic stem cell (HSC) expansion. Additionally, post-transplant DR reshaped the gut microbiotas of the recipient mice, which inhibited inflammatory responses and thus may have contributed to maintaining HSC function. Our findings may have important implications for clinical work because reduced food intake and problems with digestion and absorption are common in patients undergoing HCT. Graphical Abstract

Calibration of the Solar X-ray Detector on-board the Macao Science Satellite-1B for Soft X-ray Detection - Man-Hei Ng; Xiaoping Zhang; Jianwu Chen; Yongqiang Shi; Fuchang Zuo; Wenxi Peng; Weichun Fu; Liansheng Li; Pengwei Luo; Chi-Long Tang; Guozheng Zhang; Zhiwu Mei; et al. (Science China Earth Sciences, 2025)

Mechanism of flavonols for binding protein and inhibiting cell activity: Regulation by B-ring hydroxyl groups and Cu(II) coordination - Qinhao Guan; Lihua Tang; Man Xu; Liangliang Zhang; Lixin Huang; Mohd Shahnawaz Khan (Food Bioscience, 2024)

Sexual differentiation and juvenile hermaphroditism in silver pomfrets: Direction, process, and dietary factors - Yaya Li; Mingzhe Yuan; Peng Shi; Keyan Cai; Jiabao Hu; Man Zhang; Youyi Zhang; Yuanbo Li; Mengke Tang; Zukang Feng; Chunlai Qin; Wei Ge; et al. (Aquaculture, 2024)

Remediation of AMD based on hydrogeochemical zonation: A typical metal mine in China - Jie Tang; Xin Liu; Bo Li; Yuhan Nie; Xin Gao; Man Gao; Guo Liu (Science of The Total Environment, 2024)

Potentially toxic element source apportionment and risk assessment in agricultural soils around a large-scale Pb-Zn mine in Southwest China - Heng Wei; Xuekui Niu; Minmin Li; Canwen Cui; Zhonghua Wei; Wei Long; Man Tang; Hong Yu; Peng Zhang; Liping He; Bo Pan (Journal of Environmental Chemical Engineering, 2024)

Probing trace of intracellularly-originated hydrogen peroxide based Pt–Cd bimetallic nanozyme on an enzyme-free electrochemical sensor - Man Xu; Zhichao Yu; Qiaohua Wei; Dianping Tang (Analytica Chimica Acta, 2024)

Simulated cold spell: Changes of lipid metabolism on silver pomfret during cooling and rewarming - Man Zhang; Jiabao Hu; Jiajie Zhu; Mengke Tang; Youyi Zhang; Yaya Li; Weiwei Gu; Huan Jiang; Danli Wang; Shanliang Xu; Xiaojun Yan; Yajun Wang (Aquaculture, 2024)

The complexity of structural variations in Brassica rapa revealed by assembly of two complete T2T genomes - Yifan Zhou; Hanzhe Ye; Enwei Liu; Jingjing Tian; Liping Song; Zhiyong Ren; Man Wang; Zhenghui Sun; Liguang Tang; Zhongyue Ren; Jinquan Li; Qijun Nie; et al. (Science Bulletin, 2024)

Amine response smartphone-based portable and intelligent polyvinyl alcohol films for real-time detection of shrimp freshness - Man Luo; Ji Liu; Yating Zhang; Tao Wang; Xiaomei Ren; Lijuan Gui; Junyuan Zhao; Xuwei Zhang; Yunqing Tang; Ziting Zeng; Fengzhen Hou; Qifeng Zhong; et al. (Food Chemistry, 2024)

Serum LDL Promotes Microglial Activation and Exacerbates Demyelinating Injury in Neuromyelitis Optica Spectrum Disorder - Man Chen; Yun-Hui Chu; Wen-Xiang Yu; Yun-Fan You; Yue Tang; Xiao-Wei Pang; Hang Zhang; Ke Shang; Gang Deng; Luo-Qi Zhou; Sheng Yang; Wei Wang; et al. (Neuroscience Bulletin, 2024)
Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune inflammatory demyelinating disease of the central nervous system (CNS) accompanied by blood-brain barrier (BBB) disruption. Dysfunction in microglial lipid metabolism is believed to be closely associated with the neuropathology of NMOSD. However, there is limited evidence on the functional relevance of circulating lipids in CNS demyelination, cellular metabolism, and microglial function. Here, we found that serum low-density lipoprotein (LDL) was positively correlated with markers of neurological damage in NMOSD patients. In addition, we demonstrated in a mouse model of NMOSD that LDL penetrates the CNS through the leaky BBB, directly activating microglia. This activation leads to excessive phagocytosis of myelin debris, inhibition of lipid metabolism, and increased glycolysis, ultimately exacerbating myelin damage. We also found that therapeutic interventions aimed at reducing circulating LDL effectively reversed the lipid metabolic dysfunction in microglia and mitigated the demyelinating injury in NMOSD. These findings shed light on the molecular and cellular mechanisms underlying the positive correlation between serum LDL and neurological damage, highlighting the potential therapeutic target for lowering circulating lipids to alleviate the acute demyelinating injury in NMOSD.

Construction of blackberry polysaccharide nano-selenium particles: Structure features and regulation effects of glucose/lipid metabolism in HepG2 cells - Dou Zu-Man; Zhang Yu-Long; Tang Chun-Yang; Liu Chuang; Fang Jia-Qin; Huang Qiang; Chen Chun; You Li-Jun; Tan Chin-Ping; Niu Hui; Fu Xiong (Food Research International, 2024)

Enhanced interfacial stability of Pt/TiO2/Ti via Pt-O bonding for efficient acidic electrolyzer - Haifeng Yuan; Jiawei Li; Zhenfei Tang; Yujie Wang; Tong Wu; Man Huang; Lili Zhao; Zhenhuan Zhao; Hong Liu; Caixia Xu; Xiaoyan Liu; Weijia Zhou (Chemical Engineering Journal, 2024)

Subalpine peatland development since the Last Glacial Maximum in subtropical China: Predominantly controlled by monsoonal climate and local topography - Cong Chen; Kangyou Huang; Dehao Xie; Meiling Man; Yongjie Tang; Yuanfu Yue; Xiao Zhang; Zhuo Zheng; Rachid Cheddadi (CATENA, 2024)

Rate-dependent shear behaviors of rock discontinuities with different joint wall strengths - Zhifei Zhang; Man Huang; Zhi Cheng Tang (Bulletin of Engineering Geology and the Environment, 2024)

Chronic Fluoride Exposure Induces Ovarian Dysfunction and Potential Association with Premature Ovarian Failure in Female Rats - Xiaoke Tang; Hongjuan Li; Yali Wang; Li Zeng; Ling Long; Yajun Qu; Hui Yang; Xiaolin Zhang; Yanmin Li; Yanni Yu; Qi Zhou; Man Luo (Biological Trace Element Research, 2024)

Arbuscular mycorrhizal fungi attenuate negative impact of drought on soil functions - Bo Tang; Jing Man; Anika Lehmann; Matthias C. Rillig (Global Change Biology, 2024)
Although positive effects of arbuscular mycorrhizal (AM) fungi on plant performance under drought have been well documented, how AM fungi regulate soil functions and multifunctionality requires further investigation. In this study, we first performed a meta‐analysis to test the potential role of AM fungi in maintaining soil functions under drought. Then, we conducted a greenhouse experiment, using a pair of hyphal ingrowth cores to spatially separate the growth of AM fungal hyphae and plant roots, to further investigate the effects of AM fungi on soil multifunctionality and its resistance against drought. Our meta‐analysis showed that AM fungi promote multiple soil functions, including soil aggregation, microbial biomass and activities of soil enzymes related to nutrient cycling. The greenhouse experiment further demonstrated that AM fungi attenuate the negative impact of drought on these soil functions and thus multifunctionality, therefore, increasing their resistance against drought. Moreover, this buffering effect of AM fungi persists across different frequencies of water supply and plant species. These findings highlight the unique role of AM fungi in maintaining multiple soil functions by mitigating the negative impact of drought. Our study highlights the importance of AM fungi as a nature‐based solution to sustaining multiple soil functions in a world where drought events are intensifying.

Mycorrhization enhances plant growth and stabilizes biomass allocation under drought - Bo Tang; Jing Man; Ferran Romero; Joana Bergmann; Anika Lehmann; Matthias C. Rillig (Global Change Biology, 2024)
Plants and their symbionts, such as arbuscular mycorrhizal (AM) fungi, are increasingly subjected to various environmental stressors due to climate change, including drought. As a response to drought, plants generally allocate more biomass to roots over shoots, thereby facilitating water uptake. However, whether this biomass allocation shift is modulated by AM fungi remains unknown. Based on 5691 paired observations from 154 plant species, we conducted a meta‐analysis to evaluate how AM fungi modulate the responses of plant growth and biomass allocation (e.g., root‐to‐shoot ratio, R/S) to drought. We found that AM fungi attenuate the negative impact of drought on plant growth, including biomass production, photosynthetic performance and resource (e.g. nutrient and water) uptake. Accordingly, drought significantly increased R/S in non‐inoculated plants, but not in plants symbiotic with established AM fungal symbioses. These results suggest that AM fungi promote plant growth and stabilize their R/S through facilitating nutrient and water uptake in plants under drought. Our findings highlight the crucial role of AM fungi in enhancing plant resilience to drought by optimizing resource allocation. This knowledge opens avenues for sustainable agricultural practices that leverage symbiotic relationships for climate adaptation.

Comparison of binding sites and affinity of flavonol–Cu(II) complexes with the same parent nucleus: Synthesis, DFT prediction, and coordination pattern - Qinhao Guan; Lihua Tang; Man Xu; Liangliang Zhang; Lixin Huang; Mohd Shahnawaz Khan (Food Chemistry, 2024)

Potential scalable fabrication of high-performance photothermal fabric via chemical dyeing for solar-powered brine distillation - Deng Lin; Man Yang; Qiuhan Sun; Xiaoyan Tang; Jingye Li; Hongjuan Ma; Bowu Zhang (Desalination, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Exploration of natural processes and anthropogenic inputs by Zn isotopes in suspended particulate matter: A case study from the Lancang River in Southwest China - Yang Tang; Guilin Han; Rui Qu; Jinke Liu; Man Liu (Environmental Pollution, 2024)

Effect of light intensity on the accumulation of protostane triterpenes in Asian water plantain (Alisma orientale) - Wenqing Wu; Simeng Li; Wei Gu; Rong Tian; Man Luo; Junjie Tang; Min Tang; Yinzhi Wu (Acta Physiologiae Plantarum, 2024)

Unique ternary Pd/NH2-MIL-125/CdIn2S4 composite expands the absorption range of visible light and improves H2 evolution efficiency - Man Zhang; Kangzheng Li; Zhe Yin; Zhichao Zhang; Qingcheng Luo; Binglin Tang; Guoping Yu; Tianding Hu; Shaoyun Shan (Journal of Environmental Chemical Engineering, 2024)

Piperlongumine inhibits esophageal squamous cell carcinoma in vitro and in vivo by triggering NRF2/ROS/TXNIP/NLRP3-dependent pyroptosis - Yue Cui; Xiao-bo Chen; Ying Liu; Qian Wang; Jie Tang; Man-jun Chen (Chemico-Biological Interactions, 2024)

Identifying priorities under highly heterogeneous environments through species distribution models to facilitate orchid conservation - Xue-Man Wang; Ying Tang; Xue-Feng Peng; Juan Wang; Shi-Qi Zhang; Yu Feng; Pei-Hao Peng (Biodiversity and Conservation, 2024)

Immune response of silver pomfret (Pampus argenteus) to Photobacterium damselae subsp. Damselae: Virulence factors might induce immune escape by damaging phagosome - Youyi Zhang; Jiabao Hu; Kaiheng Yan; Feirong Yuan; Yuanbo Li; Man Zhang; Yaya Li; Xiang Huang; Jie Tang; Danli Wang; Shanliang Xu; Suming Zhou; et al. (Aquaculture, 2024)

Mitigation effects of foliar supply of different sulfur forms on uptake, translocation and grain accumulation of Cd and As by paddy rice on basis of liming - Aijun Yao; Jingliu Yang; Ying Liu; Guangquan Su; Man Zhao; Shizhong Wang; Yetao Tang; Rongliang Qiu (Science of The Total Environment, 2023)

Insights into the effects of natural pyrite-activated sodium percarbonate on tetracycline removal from groundwater: Mechanism, pathways, and column studies - Liu Guo; Ziqiu Nie; Lijia Wen; Bohan Chen; Jie Tang; Man Gao; Jiajing Chen; Jingjing Liu (Science of The Total Environment, 2023)

Cold Stress Induces Apoptosis in Silver Pomfret via DUSP-JNK Pathway - Jiabao Hu; Man Zhang; Kaiheng Yan; Youyi Zhang; Yaya Li; Jiajie Zhu; Guanlin Wang; Xiangbing Wang; Yuanbo Li; Xiang Huang; Jie Tang; Rongyue Zheng; et al. (Marine Biotechnology, 2023)

Arbuscular mycorrhizal fungi benefit plants in response to major global change factors - Bo Tang; Jing Man; Anika Lehmann; Matthias C. Rillig (Ecology Letters, 2023)
Land plants play a key role in global carbon cycling, but the potential role of arbuscular mycorrhizal fungi (AMF) in the responses of a wide range of plant species to global change factors (GCFs) remains limited. Based on 1100 paired observations from 181 plant species, we conducted a meta‐analysis to test the role of AMF in plant responses to four GCFs: drought, warming, nitrogen (N) addition and elevated CO 2 . We show that AMF significantly ameliorate the negative effects of drought on plant performance. The GCFs N addition and elevated CO 2 significantly enhance the performance of AM plants but not of non‐inoculated plants. AM plants show better performance than their non‐inoculated counterparts under warming, although neither of them showed a significant response to this GCF. These results suggest that AMF benefit plants in response to GCFs. Our study highlights the importance of AMF in enhancing plant performance under ongoing global change.

Seismic response and failure modes analysis of pile foundations in liquefiable soils using various design criteria - Xiaofeng Man; Liang Tang; Xijun Jia; Shengyi Cong; Xianzhang Ling (Soil Dynamics and Earthquake Engineering, 2023)

Contribution of the bacterial community of poorly fermented oat silage to biogas emissions on the Qinghai Tibetan Plateau - Chaosheng Liao; Binbin Na; Xiaolong Tang; Man Zhao; Changbing Zhang; Shiyong Chen; Minghong You; Binqiang Bai; Lizhuang Hao; Dorjeeh Tondrob; Guangpeng Qu; Shuqing Yang; et al. (Science of The Total Environment, 2023)

Efficient genome editing in cotton using the virus-mediated CRISPR/Cas9 and grafting system - Wei-Feng Guo; Dan-Dan Guo; Fen Li; Shen-Zhai Shang; Ting-Wan Li; Ying-Chao Tang; Man Jiang; Fu-Chun Xu; Wei Gao (Plant Cell Reports, 2023)

Red mud-derived iron carbon catalyst for the removal of organic pollutants in wastewater - Yawen Fei; Ning Han; Junjie Shi; Shiyu Tang; Hezhen Zhuang; Longyu Wang; Jincheng Ran; Enxia Gao; Mohamed A. Habila; Zhijie Chen; Dongping Tao; Bing-Jie Ni; et al. (Chemosphere, 2023)

Natural polysaccharides protect against diet-induced obesity by improving lipid metabolism and regulating the immune system - Chao Tang; Yuxin Wang; Dan Chen; Man Zhang; Jingguo Xu; Chen Xu; Jun Liu; Juan Kan; Changhai Jin (Food Research International, 2023)

Identification and characterization of toll-like receptor genes in silver pomfret (Pampus argenteus) and their involvement in the host immune response to Photobacterium damselae subsp. Damselae and Nocardia seriolae infection - Yuanbo Li; Jiabao Hu; Youyi Zhang; Kaiheng Yan; Man Zhang; Yaya Li; Xiang Huang; Jie Tang; Tingyan Yao; Danli Wang; Shanliang Xu; Xubo Wang; et al. (Fish & Shellfish Immunology, 2023)

Simultaneous detection of multiple influenza virus subtypes based on microbead-encoded microfluidic chip - Shao-Li Hong; Xuan Wang; Zhong-Hua Bao; Meng-Fan Zhang; Man Tang; Nangang Zhang; Huihong Liu; Zi-Yuan Zhu; Kan Liu; Zhi-Liang Chen; Wei Li (Analytica Chimica Acta, 2023)

Construction of an ecological security network in the Fenhe River Basin and its temporal and spatial evolution characteristics - Hailong Liu; Zhenglei Wang; Liping Zhang; Fei Tang; Gaiyan Wang; Man Li (Journal of Cleaner Production, 2023)

Savanna/rainforest dynamics and hydroclimate changes in northern boundary of tropical Asia over the past 150 kyrs - Cong Chen; Kangyou Huang; Zhuo Zheng; Yongqiang Zong; Peter Kershaw; Shixiong Yang; Liping Tian; Meiling Man; Sheng-Hua Li; Chris Brodie; Ning Wang; Xiao Zhang; et al. (Global and Planetary Change, 2023)

Characterizing the remobilization flux of cadmium from pre-anthesis vegetative pools in rice during grain filling using an improved stable isotope labeling method - Bo-Fang Yan; Cheng-Feng Hu; Man Zhao; Rong-Liang Qiu; Ye-Tao Tang (Environmental Pollution, 2023)

An oxidoreductase gene CtnD involved in citrinin biosynthesis in Monascus purpureus verified by CRISPR/Cas9 gene editing and overexpression - Guangfu Tang; Haiqiao Man; Jiao Wang; Jie Zou; Jiehong Zhao; Jie Han (Mycotoxin Research, 2023)

Two new isoquinolines from Corydalis saxicola - Zhi-Wei Ouyang; Ji-Man He; Feng Qin; Ling Li; Wen-Di Tang; Dian-Peng Li; Jiang-Ke Qin (Natural Product Research, 2023)

Multistage treatment of bamboo powder waste biomass: Highly efficient and selective isolation of lignin components - Man Zhang; Rubo Tian; Siyang Tang; Kejing Wu; Binshen Wang; Yingying Liu; Yingming Zhu; Houfang Lu; Bin Liang (Waste Management, 2023)

Co-transport of biochar nanoparticles (BC NPs) and rare earth elements (REEs) in water-saturated porous media: New insights into REE fractionation - Quan Wan; Beibei Liu; Miaoyue Zhang; Man Zhao; Yuan Dai; Wenshen Liu; Kengbo Ding; Qingqi Lin; Zhuobiao Ni; Jingjing Li; Shizhong Wang; Chao Jin; et al. (Journal of Hazardous Materials, 2023)

Fe contents and isotopes in suspended particulate matter of Lancang River in Southwest China - Yang Tang; Guilin Han; Liu Man; Jie Zeng; Rui Qu (Science of The Total Environment, 2023)

Experimental and numerical investigations on the explosions nearby a free surface from both sides - Hao Tang; Zhao-Li Tian; Xin-Yang Ju; Ji-Tuan Feng; Yun-Long Liu; A-Man Zhang (Ocean Engineering, 2023)

A portable holey carbon nitride/3D Ag facilely self-assembled on copper sheet for dramatically enhanced SERS and photocatalytic performance - Lixia Qin; Min Tang; Hui Shen; Man Luo; Jian-Wei Tao; Taiyang Zhang; Shi-Zhao Kang; Xiangqing Li (Chemical Engineering Journal, 2023)

Transportation of citrinin is regulated by the CtnC gene in the medicinal fungus Monascus purpureus - Yanling Gui; Guangfu Tang; Haiqiao Man; Jiao Wang; Jie Han; Jiehong Zhao (Journal of Zhejiang University-SCIENCE B, 2023)

The acid dissolution characteristics of cadmium fixed by a novel Ca-Fe-Si composite material - Aijun Yao; Xiang Guo; Man Zhao; Shizhong Wang; Yetao Tang; Rongliang Qiu (Journal of Environmental Sciences, 2023)

High-efficiency continuous-flow microwave heating system based on metal-ring resonant structure - Man Liu; Danfeng Zhou; Yu Peng; Zhengming Tang; Kama Huang; Tao Hong (Innovative Food Science & Emerging Technologies, 2023)

Are human exposure assessment the same for non-persistent organic chemicals? -from the lens of urinary variability and predictability - Man Deng; Tianrui Gao; Lin Tao; Weitian Tang; Xinying Wang; Ye Jiang; De-Xiang Xu; Mingliang Fang; Yichao Huang (Science of The Total Environment, 2023)

Restored vegetation is more resistant to extreme drought events than natural vegetation in Southwest China - Ying Liu; Zhi Ding; Yanan Chen; Fengqin Yan; Pujia Yu; Weidong Man; Mingyue Liu; He Li; Xuguang Tang (Science of The Total Environment, 2023)

Electrophysiological microenvironment and site-specific cell behaviors regulated by fibrous aniline trimer-based polyurethanes in bone progressive regeneration - Jiajing Tang; Yinglong Zhang; Wei Fang; Yi Man; Jinzheng Zhang; Qing Zhao; Xiaoyu Lei; Jieqiong Chen; Jidong Li; Yubao Li; Yi Zuo (Chemical Engineering Journal, 2023)

Self-destructive microchip: Support-free energetic film of BiOBr/Al/Bi2O3 nanothermites and its destructive performance - Haifeng Yang; Zhiqiang Qiao; Weimiao Wang; Pengfei Tang; Shuaishuai Man; Xiaodong Li; YuTing Xie; Deyun Tang; Xueming Li; Guangcheng Yang (Chemical Engineering Journal, 2023)

Investigation of toxic effect of mercury on Microcystis aeruginosa: Correlation between intracellular mercury content at single cells level and algae physiological responses - Wenxiao Tang; Man He; Beibei Chen; Gang Ruan; Yixue Xia; Pingping Xu; Gaofei Song; Yonghong Bi; Bin Hu (Science of The Total Environment, 2023)

Electro-assisted catalytic oxidation of flue gas desulfurization-derived magnesium sulfite using cobalt ferrite as catalyst under moderate condition - Hongjing Tian; Yixing Che; Shengnan Xu; Jixing Tang; Hui Wang; Man Wu; Qingjie Guo (Journal of Cleaner Production, 2023)

Construction of novel Heat-conducting Cu-based MOF nanocomposite (HK-mBNNS/PVDF) film for highly efficient Ad-/desorption of toluene - Junjie Li; Liming Liu; Syed Jalil Shah; Ying Tang; Shanliang Jiang; Guangyuan Mu; Quanru Man; Zhongxing Zhao; Zhenxia Zhao (Chemical Engineering Journal, 2023)

Stitching electron localized heptazine units with “carbon patches” to regulate exciton dissociation behavior of carbon nitride for photocatalytic elimination of petroleum hydrocarbons - Qi Guo; Yuning Wu; Linhong Xia; Xue-Fang Yu; Kaisheng Zhang; Yujie Du; Lixue Zhang; Hua Tang; Jianbo Cheng; Jianpeng Shang; Yanhua Peng; Zhuo Li; et al. (Chemical Engineering Journal, 2023)

Underwater self-sustaining combustion and micro-propulsion properties of Al@FAS-17/PTFE-based direct-writing nanothermite - Haifeng Yang; Chuanhao Xu; Weimiao Wang; Pengfei Tang; Xiaodong Li; Shanshan He; Hebin Bao; Shuaishuai Man; Deyun Tang; Xueming Li; Guangcheng Yang; Zhiqiang Qiao (Chemical Engineering Journal, 2023)

Plants boost pyrrhotite-driven nitrogen removal in constructed wetlands - Cheng Shen; Liti Su; Yaqian Zhao; Wenbo Liu; Ranbin Liu; Fuhao Zhang; Yun Shi; Jie Wang; Qiuqi Tang; Yan Yang; Yu Bon Man; Jin Zhang (Bioresource Technology, 2023)

Failure mechanism and treatment measures of supporting structures at the portal for a shallow buried and asymmetrically loaded tunnel with small clear-distance - Hao Chen; Hongpeng Lai; Man Huang; Gang Wang; Qiang Tang (Natural Hazards, 2022)

Dyadobacter diqingensis sp. nov., isolated from Baima snow mountain of Diqing Tibetan Autonomous Prefecture in Yunnan province, south-west China - Lei Ran; Man Peng; Wei-Qun Wang; Yu-Zhou Feng; Juan Wang; Yu Wang; Cui-Ying Li; Xin-Xing Liu; Wei-Xun Chunyu; Shu-Kun Tang (Archives of Microbiology, 2022)

Alleviating the Influence of Circadian Rhythms and Drug Properties to the Release of Paliperidone Gel Matrix Tablets with Compression Coating Technology and Microenvironment Shaping - Zherui Zhang; Shumin Chen; Man Wen; Haibing He; Yu Zhang; Tian Yin; Jingxin Gou; Xing Tang (AAPS PharmSciTech, 2022)

Bone Marrow-Derived Alk1 Mutant Endothelial Cells and Clonally Expanded Somatic Alk1 Mutant Endothelial Cells Contribute to the Development of Brain Arteriovenous Malformations in Mice - Sonali S. Shaligram; Rui Zhang; Wan Zhu; Li Ma; Man Luo; Qiang Li; Miriam Weiss; Thomas Arnold; Nicolas Santander; Rich Liang; Leandro do Prado; Chaoliang Tang; et al. (Translational Stroke Research, 2022)

LbAMT3-1, an ammonium transporter induced by arbuscular mycorrhizal in Lycium barbarum, confers tobacco with higher mycorrhizal levels and nutrient uptake - Kang Cheng; Man Wei; Xiaoxia Jin; Ming Tang; Haoqiang Zhang (Plant Cell Reports, 2022)

Potential Application of Biosurfactant-Producing Bacteria for Bioremediation of Oil Polluted Marine Intertidal Sediments - Ping Guo; Wei-Wei Xu; Dan-Na Wei; Man-Xia Zhang; Jin Zhang; Shi Tang; Bin-Xia Cao; Jian-Guo Lin; Wei Li (Journal of Marine Science and Engineering, 2022)
The removal of oil contaminants in marine intertidal sediments under cold climate is an urgent issue. Although the bioavailability of petroleum hydrocarbons decreases at low temperatures, biosurfactants can promote oil biodegradation. In this study, characteristics of biosurfactants produced by cold-adapted oil-degrading bacteria Planococcus sp. XW-1 were studied. Adding the XW-1 biosurfactant could effectively facilitate the solubility of phenanthrene, pyrene, diesel oil, and crude oil. The solubilization was limited by the number of rings and the molecular weight (WSRphenanthrene = 0.0234; WSRpyrene = 0.0165; WSRdiesel oil = 0.0027; WSRcrude oil = 0.0015). Additional biosurfactants significantly washed out crude oil adsorbed to the sand (reduction from 17.1%, 22.7% to 87.9% and 94.28% in 24 h). With the increase in particle size, the removal efficiency increased from 87.9% to 94.28%. After the addition of biosurfactant, the effect of degradation increased by 20% in 20 days. The results suggest that the biosurfactant-producing bacteria Planococcus sp. XW-1 is a promising candidate used in the in situ bioremediation of petroleum-contaminated intertidal sediment.

Revising the species diversity of Hygrophorus section Olivaceoumbrini s.l. (Hygrophoraceae, Agaricales) in China - Hong-Yan Huang; Wen-Hao Zhang; Ting Huang; Shuai Jiang; Yan-Jia Hao; Man Mu; Li-Ping Tang (Mycological Progress, 2022)

Caldalkalibacillus salinus sp. nov., isolated from a salt lake in Xinjiang, northwest China - Ting-Hao Ouyang; Man Peng; Zhen Zhang; Wei-Xun Chunyu; Li-Ming Wang; En-Min Zhou; Xu-Hong Gao; Shu-Kun Tang (Archives of Microbiology, 2022)

A contribution to knowledge of Gyroporus (Gyroporaceae, Boletales) in China: three new taxa, two previous species, and one ambiguous taxon - Hui-Jing Xie; Li-Ping Tang; Man Mu; Yu-Guang Fan; Shuai Jiang; Ming-Sheng Su; Zhi-Qun Liang; Nian-Kai Zeng (Mycological Progress, 2022)

Propioniciclava soli sp. nov., isolated from forest soil, Yunnan, China, and reclassification of the genus Brevilactibacter into the genus Propioniciclava, and Brevilactibacter sinopodophylli, Brevilactibacter flavus, and Brevilactibacter coleopterorum as Propioniciclava sinopodophylli comb. nov., Propioniciclava flava comb. nov., and Propioniciclava coleopterorum comb. nov., respectively - Le-Le Li; Jiang-Yuan Zhao; Yu Geng; Yu-Guang Zhou; Hui-Ren Yuan; Man Cai; Meng-Liang Wen; Ming-Gang Li; Shu-Kun Tang (Archives of Microbiology, 2022)

A comprehensive analysis of gorilla-specific LINE-1 retrotransposons - Soyeon Jeon; Songmi Kim; Man Hwan Oh; Ping Liang; Wanxiangfu Tang; Kyudong Han (Genes & Genomics, 2021)

Arbuscular Mycorrhizal Fungi Mediate Grazing Effects on Seasonal Soil Nitrogen Fluxes in a Steppe Ecosystem - Bo Tang; Jing Man; Ruoyu Jia; Yang Wang; Yongfei Bai (Ecosystems, 2021)

Alkalibacillus aidingensis sp. nov., an Bacterium Isolated from Aiding Lake in Xinjiang Province, North-West China - Rui Li; Li Yang; Rüdiger Pukall; Meina Neumann-Schaal; Chang-Gai Mu; Yong-Jiang Shi; Yun Wang; Gang-Qiang Jiang; Yu-Guang Zhou; Man Cai; Min Yin; Wen-Yong Zhu; et al. (Current Microbiology, 2021)

Heavy grazing disrupts positive effects of arbuscular mycorrhizae symbiosis on community productivity and stability under low and high phosphorus conditions - Bo Tang; Jing Man; Guanhai Xiang; Yang Wang; Yongfei Bai (Plant and Soil, 2020)

Numerical study of the building pressure cycling method for evaluating vapor intrusion from groundwater contamination - Yanqiu Liu; Jun Man; Yue Wang; Yuting Xiao; Wei Tang; Qiang Chen; Yijun Yao (Environmental Science and Pollution Research, 2020)

Preface - Yu Bon Man; Yuanyuan Tang; Ka Lai Chow; Tsz Fung Wong (Environmental Geochemistry and Health, 2020)

Optimization of an mRNA vaccine assisted with cyclodextrin-polyethyleneimine conjugates - Lu Tan; Tao Zheng; Man Li; Xiaofang Zhong; Yao Tang; Ming Qin; Xun Sun (Drug Delivery and Translational Research, 2020)

Photosynthetic bacteria enhanced water quality and integrity of microbial community composition of integrated multitrophic aquaculture system of milkfish Chanos chanos coastal farming - Chingwen Ying; Man-Jung Chang; Yi-Tang Chang; Wei-Liang Chao; Shinn-Lih Yeh; Jih-Tay Hsu (Fisheries Science, 2020)

APOD mission status and preliminary results - Geshi Tang; Xie Li; Jianfeng Cao; Shushi Liu; Guangming Chen; Haijun Man; Xiaomin Zhang; Sihan Shi; Ji Sun; Yongping Li; Andres Calabia (Science China Earth Sciences, 2020)

Preparation, Characterization, and Properties of Inclusion Complexes of Balofloxacin with Cyclodextrins - Xiuyun Ren; Hongyun Qian; Peixiao Tang; Yuling Tang; Yuanyuan Liu; Hongyu Pu; Man Zhang; Ludan Zhao; Hui Li (AAPS PharmSciTech, 2019)

QTL analysis and candidate gene identification for plant height in cotton based on an interspecific backcross inbred line population of Gossypium hirsutum × Gossypium barbadense - Jianjiang Ma; Wenfeng Pei; Qifeng Ma; Yanhui Geng; Guoyuan Liu; Ji Liu; Yupeng Cui; Xia Zhang; Man Wu; Xingli Li; Dan Li; XinShan Zang; et al. (Theoretical and Applied Genetics, 2019)

Tumor-Targeted Chemoimmunotherapy with Immune-Checkpoint Blockade for Enhanced Anti-Melanoma Efficacy - Man Li; Yuting Yang; Chaoqun Xu; Jiaojie Wei; Yingke Liu; Xingli Cun; Qianwen Yu; Xian Tang; Sheng Yin; Zhirong Zhang; Qin He (The AAPS Journal, 2019)

Hepatitis E virus infection in Wuhan, Central China - Wei-Feng Tang; De-Guang Kong; Yuan-Hong Wang; Man-Qing Liu; Quan Hu (Archives of Virology, 2019)

Sorption-desorption behaviors of heavy metals by biochar-compost amendment with different ratios in contaminated wetland soil - Zhaoxue Yang; Jie Liang; Lin Tang; Guangming Zeng; Man Yu; Xiaodong Li; Xuemei Li; Yingying Qian; Haipeng Wu; Yuan Luo; Dan Mo (Journal of Soils and Sediments, 2018)

Gracilibacillus eburneus sp.nov., a moderately halophilic bacterium isolated from Xinjiang province, China - Hui-Lin Guan; Yun-Jiao Zhang; Xiao-Ju Lu; Man Jia; Zheng-Yun Zhang; Xu-Hong Gao; Yong-Chun Ma; Fei Tian; Shu-Kun Tang (Archives of Microbiology, 2018)

Actionable secondary findings from whole-genome sequencing of 954 East Asians - Clara Sze-man Tang; Saloni Dattani; Man-ting So; Stacey S. Cherny; Paul K. H. Tam; Pak C. Sham; Maria-Mercè Garcia-Barcelo (Human Genetics, 2018)

‘One Health’ for the people of Hong Kong and the world - Kin-Hang Kok; Hei-Man Vincent Tang; Dong-Yan Jin (Science China Life Sciences, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Effects of light intensity on leaf photosynthetic characteristics, chloroplast structure, and alkaloid content of Mahonia bodinieri (Gagnep.) Laferr. - De-Xin Kong; Yan-Qun Li; Man-Lian Wang; Mei Bai; Rong Zou; Hui Tang; Hong Wu (Acta Physiologiae Plantarum, 2016)

Phase 1 clinical trial demonstrated that MUC1 positive metastatic seminal vesicle cancer can be effectively eradicated by modified Anti-MUC1 chimeric antigen receptor transduced T cells - Fengtao You; Licui Jiang; Bozhen Zhang; Qiang Lu; Qiao Zhou; Xiaoyang Liao; Hong Wu; Kaiqi Du; Youcai Zhu; Huimin Meng; Zhishu Gong; Yunhui Zong; et al. (Science China Life Sciences, 2016)

Neuroprotection of Sevoflurane Against Ischemia/Reperfusion-Induced Brain Injury Through Inhibiting JNK3/Caspase-3 by Enhancing Akt Signaling Pathway - Xiang-Ru Wen; Yan-Yan Fu; Hong-Zhi Liu; Jian Wu; Xiao-Ping Shao; Xun-Bao Zhang; Man Tang; Yue Shi; Kai Ma; Fang Zhang; Yi-Wen Wang; Hui Tang; et al. (Molecular Neurobiology, 2016)

The synergistic effect of 5Azadc and TSA on maintenance of pluripotency of chicken ESCs by overexpression of NANOG gene - Xiaoyan Wang; Yingjie Wang; Qisheng Zuo; Dong Li; Wenhui Zhang; Chao Lian; Beibei Tang; Tianrong Xiao; Man Wang; Kehua Wang; Bichun Li; Yani Zhang (In Vitro Cellular & Developmental Biology - Animal, 2016)

Skermanella rubra sp. nov., a bacterium isolated from the desert of Xinjiang, China - Zheng-Yun Zhang; Xu-Hong Gao; Yun-Jiao Zhang; Man Jia; Xiao-Ju Lu; Yong-Chun Ma; Fei Tian; Qiong Xie; Shu-Kun Tang (Antonie van Leeuwenhoek, 2015)

Jonesia luteola sp. nov., a bacterium isolated from Xinjiang Province, China - Yong Li; Yun-Jiao Zhang; Yong-Chun Ma; Zhi-Lian Gong; Man Jia; Fei Tian; Hans-Peter Klenk; Shu-Kun Tang (Antonie van Leeuwenhoek, 2015)

Projection of the Zhujiang (Pearl) River Delta’s potential submerged area due to sea level rise during the 21st century based on CMIP5 simulations - Jiangjiang Xia; Zhongwei Yan; Wen Zhou; Soi Kun Fong; Ka Cheng Leong; Iu Man Tang; S. W. Chang; W. K. Leong; Shaofei Jin (Acta Oceanologica Sinica, 2015)

Plastorhodobacter daqingensis gen. nov., sp. nov.: A Non-phototrophic Bacterium Isolated from Daqing Oilfield - Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Yue-Qin Tang; Ya-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2015)

Erratum to: Negadavirga shengliensis gen. nov., sp. nov., a novel member of the family Cyclobacteriaceae isolated from oil-contaminated saline soil - Bing Hu; Qian Yang; Man Cai; Yue-Qin Tang; Gui-Fang Zhao; Xiao-Lei Wu (Antonie van Leeuwenhoek, 2015)

Hydrotubation Combined with Chinese Herbal Medicine for Salpingitic Infecundity: A Systematic Review and Meta-Analysis - Huanhuan Wen; Jinrong Fu; Hong Tang; Man Ge; Linna Feng (Cell Biochemistry and Biophysics, 2015)

Negadavirga shengliensis gen. nov., sp. nov., a novel member of the family Cyclobacteriaceae isolated from oil-contaminated saline soil - Bing Hu; Qian Yang; Man Cai; Yue-Qin Tang; Gui-Fang Zhao; Xiao-Lei Wu (Antonie van Leeuwenhoek, 2015)

Halodurantibacterium flavum gen. nov., sp. nov., a Non-phototrophic Bacterium Isolated from an Oil Production Mixture - Xiang-Lin Lv; Bai-Sheng Xie; Man Cai; Yue-Qin Tang; Ya-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2015)

Seohaeicola nanhaiensis sp. nov., A Moderately Halophilic Bacterium Isolated from the Benthic Sediment of South China Sea - Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Yue-Qin Tang; Yan-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2014)

Expression of TGF-β1, SNAI1 and MMP-9 is associated with lymph node metastasis in papillary thyroid carcinoma - Ni Wang; Rong Jiang; Jun-Yan Yang; Cui Tang; Lei Yang; Man Xu; Qi-Feng Jiang; Zhi-Min Liu (Journal of Molecular Histology, 2014)

Erratum to: RET and NRG1 interplay in Hirschsprung disease - Hongsheng Gui; Wai-Kiu Tang; Man-Ting So; Petroola Proitsi; Pak C. Sham; Paul K. Tam; Elly Sau-Wai Ngan; Stacey S. Cherny; Maria-Mercè Garcia-Barceló (Human Genetics, 2014)

Calibration of the Normal Cutoff Values of Systolic Dyssynchrony of the Left Ventricular Synchronicity in Normal Subjects Using Real-Time 3-Dimensional Echocardiography and the Effects of Age and Heart Rate - Chun-Yan Ma; Shuang Liu; Qing Zhang; Jun Yang; Li Tang; Gabriel Yip; Cheuk-Man Yu (Cell Biochemistry and Biophysics, 2014)

Association of polymorphisms in the Chr18q11.2 locus with tuberculosis in Chinese population - Xingyan Wang; Nelson Leung-Sang Tang; Chi Chiu Leung; Kai Man Kam; Wing Wai Yew; Cheuk Ming Tam; Chiu Yeung Chan (Human Genetics, 2013)

RET and NRG1 interplay in Hirschsprung disease - Hongsheng Gui; Wai-Kiu Tang; Man-Ting So; Petroola Proitsi; Pak C. Sham; Paul K. Tam; Elly Sau-Wai Ngan; Stacey S. Cherny; Maria-Mercè Garcia-Barceló (Human Genetics, 2013)

Tenuibacillus halotolerans sp. nov., a novel bacterium isolated from a soil sample from a salt lake in Xinjiang, China and emended description of the genus Tenuibacillus - Xu-Hong Gao; Sheng Gao; Yu Zhou; Hui-Lin Guan; Yun-Jiao Zhang; Man Jia; Hua-Wei Huang; Dong-Xu Yang; Wen-Jun Li; Shu-Kun Tang (Antonie van Leeuwenhoek, 2013)

A review of the anticancer and immunomodulatory effects of Lycium barbarum fruit - Wai-Man Tang; Enoch Chan; Ching-Yee Kwok; Yee-Ki Lee; Jian-Hong Wu; Chun-Wai Wan; Robbie Yat-Kan Chan; Peter Hoi-Fu Yu; Shun-Wan Chan (Inflammopharmacology, 2012)

Fosinopril Attenuates the Doxorubicin-induced Cardiomyopathy by Restoring the Function of Sarcoplasmic Reticulum - Ya-chen Zhang; Yong Tang; Min Zhang; Jian Chen; Qing Zhou; Ying-gang Sun; Man-tian Chen; Wei-ping Xu (Cell Biochemistry and Biophysics, 2012)

Virgibacillus albus sp. nov., a novel moderately halophilic bacterium isolated from Lop Nur salt lake in Xinjiang province, China - Yun-Jiao Zhang; Yu Zhou; Man Ja; Rong Shi; Wei-Xun Chun-Yu; Ling-Ling Yang; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Mutations in the NRG1 gene are associated with Hirschsprung disease - Clara Sze-Man Tang; Elly Sau-Wai Ngan; Wai-Kiu Tang; Man-Ting So; Guo Cheng; Xiao-Ping Miao; Thomas Yuk-Yu Leon; Brian Man-Chun Leung; Kenneth-Jeremy W. S. Hui; Vincent Hang-Chai Lui; Yan Chen; Ivy Hau-Yee Chan; et al. (Human Genetics, 2012)

Ginsenoside-Rg1 mediates a hypoxia-independent upregulation of hypoxia-inducible factor-1α to promote angiogenesis - Kar-Wah Leung; Hoi-Man Ng; Maggie K. S. Tang; Chris C. K. Wong; Ricky N. S. Wong; Alice S. T. Wong (Angiogenesis, 2011)

Ganoderma lucidum polysaccharide peptide reduced the production of proinflammatory cytokines in activated rheumatoid synovial fibroblast - Y. W. Ho; J. S. L. Yeung; P. K. Y. Chiu; W. M. Tang; Z. B. Lin; R. Y. K. Man; C. S. Lau (Molecular and Cellular Biochemistry, 2007)

Modulation of the suppressive effect of corticosterone on adult rat hippocampal cell proliferation by paroxetine - Guang Qiu; Daiga M. Helmeste; Asanka N. Samaranayake; Wui-Man Lau; Tatia M. C. Lee; Siu-Wa Tang; Kwok-Fai So (Neuroscience Bulletin, 2007)